METHODOLOGY FOR USING SPECIALIZED TEXTS IN ENGLISH TO DEVELOP PROFESSIONAL COMPETENCE OF CHEMISTRY STUDENTS IN A DIGITAL EDUCATIONAL ENVIRONMENT - Tulanboyeva Dildoraxon Tulkinjon qizi (CANADA - SCIENTIFIC REVIEW OF THE PROBLEMS AND PROSPECTS OF MODERN SCIENCE AND EDUCATION, 2026)
This article examines the methodology of using specialized English texts to develop the professional competence of chemistry students in a digital educational environment. The study is based on the English for Specific Purposes (ESP) approach, which emphasizes the integration of language learning with students’ future professional activities. The paper proposes the ESP-CHEM-DIGITAL model that combines specialized chemistry texts, digital learning tools, and professionally oriented tasks into a unified methodological system. The model demonstrates how English language instruction can move beyond general language learning and function as a tool for professional training. The findings indicate that working with chemistry-related texts in a digital environment enhances students’ terminological accuracy, scientific thinking, professional communication skills, and readiness for successful professional activity. The proposed methodology can be effectively applied in teaching English to chemistry students and adapted for other natural science disciplines.